Teaching with poverty in mind : what being poor does to kids' brains and what schools can do about it - Jensen, Eric, 1950- (Alexandria, Va. : ASCD, 2009)
Covers why and how the effects of poverty have to be addressed in classroom teaching and school and district policy. Topics include what poverty does to children's brains and why students raised in poverty are especially subject to stressors that undermine school behavior and performance.
Understanding the nature of poverty -- How poverty affects behavior and academic performance -- Embracing the mind-set of change -- Schoolwide success factors -- Classroom-level success factors -- Instructional light and magic.
Includes bibliographical references and index.
Keywords: Poor children -- Education -- United States; Poverty -- United States; Educational equalization -- United States; Chancengleichheit; 2; Unterprivilegierung; USA; Educational equalization; Poor children -- Education; Poverty; United States